2016
DOI: 10.1542/peds.2015-2851g
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Diagnosis and Co-occurring Symptoms in Adopted Children With Autism Spectrum Disorder

Abstract: To determine whether adopted children with autism spectrum disorder (ASD) differ from the general ASD population in terms of diagnosis, internalizing and externalizing behaviors, sleep problems, and medications. METHODS:We studied 163 adoptees in the Autism Speaks Autism Treatment Network (ATN) in comparison with 5624 nonadopted ATN participants (aged 1.5-17.6 years; mean [SD] = 6.2 [3.4] years). Gender, age, race, ethnicity, IQ, and categorical Diagnostic and Statistical Manual of Mental Disorders, Fourth Edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Sleep problems contribute to heightened daytime cognitive, adaptive and behavioral problems among children and adolescents (68). The prevalence of sleep disorder related comorbidity in ASD was 19.7% in the current study based on analysis of 13 sleep study groups (18,20,23,27,36,39,40,43). Subtypes of sleep problems were not reported in most studies and were not included.…”
Section: Sleep Disorders Comorbiditymentioning
confidence: 80%
See 2 more Smart Citations
“…Sleep problems contribute to heightened daytime cognitive, adaptive and behavioral problems among children and adolescents (68). The prevalence of sleep disorder related comorbidity in ASD was 19.7% in the current study based on analysis of 13 sleep study groups (18,20,23,27,36,39,40,43). Subtypes of sleep problems were not reported in most studies and were not included.…”
Section: Sleep Disorders Comorbiditymentioning
confidence: 80%
“…Twenty nine studies consisting of ID, ADHD, anxiety disorders, disruptive behavior disorders, bipolar disorder, depressive disorders, OCD, psychotic disorders and sleep disorders prevalence were analyzed. Seven studies had subgroups which consisted of different countries, ages or registry samples (Figure 1) (5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). There were 33 study groups from 19 studies for ID (3,5,14,18,19,21,22,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), 21 study groups from 15 studies for ADHD (14,18,19,21,27,28,31,(35)(36)(37)(38)(39)…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents reported higher rates relative to clinician-reported diagnoses, although medications may be prescribed even in the absence of a documented diagnosis. Greenlee et al 14 found that a history of depression in children with ASD, as reported by parents, was more common with greater chronological age (reaching 20% in those aged 13-17 years), higher cognitive level, and in those 15 Finally Ezell et al 16 described patterns of comorbidity among children with ASD who had been adopted. Compared with other children with ASD, the adopted group had more severe parent-reported behavior and sleep problems and were more commonly prescribed psychotropic medication, emphasizing the complexity of the care needs of this population.…”
Section: Potential Conflict Of Interestmentioning
confidence: 99%